An efficient methodology to improve service negotiation in cloud environment. (2015) - Manoharan, Mohan; Selvarajan, Saraswathi
Cloud computing is one of the fast emerging technologies that rely on sharing computing resources rather than having local servers or other devices to handle applications. To reduce the cost of installing individual servers for handling several applications, cloud computing provides an environment to share the resources. The cloud can provide services based on the requesting environment. Thus, cloud computing can be termed as an environment-based service provider. Cloud-based services reduce the individual installation cost for server and are also able to improve the QoS for the user. This can be achieved by providing the configuration settings for the server to the requesting client. Using this configuration, the client can access the server through the cloud. In this paper, we propose a methodology to improve the QoS to provide better performance compared to the existing method. We can achieve this by improving various parameters to negotiate the cloud easily.